The International Diversification Puzzle Is Worse Than You Think - Baxter, Marianne; Jermann, Urban J. (American Economic Review, 1997)
Despite the growing integration of international financial markets, investors do not diversify internationally to any significant extent. We show that this "international diversification puzzle" is deepened once we consider the implications of nontraded human capital for portfolio composition. While growth rates of labor and capital income are not highly correlated within countries, we find that the returns to human capital and physical capital are very highly correlated within four OECD countries. Hedging human capital risk therefore involves a substantial short position in domestic marketable assets. A diversified world portfolio will involve a negative position in domestic marketable assets.